Dielectric and charge transport properties of the spin crossover complex [Fe(Htrz)2(trz)](BF4). Issue 2 (16th December 2013) - Lefter, Constantin; Gural'skiy, Il'ya A.; Peng, Haonan; Molnár, Gábor; Salmon, Lionel; Rotaru, Aurelian; Bousseksou, Azzedine; Demont, Philippe
Abstract Spin crossover compounds are considered to be a viable alternative for creating display, memory and switching devices due to the bistability of their magnetic, optical, mechanical and electrical properties. This Letter presents the study of the dielectric and transport properties of the [Fe(Htrz)2(trz)](BF4) (Htrz = 1H‐1, 2, 4‐triazole) complex in a wide temperature and frequency range. Our results reveal a singular behavior of the dielectric modulus upon the spin transition in conjunction with the switching of the conductivity between the high spin and low spin states. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)